2018
DOI: 10.1097/md.0000000000011227
|View full text |Cite
|
Sign up to set email alerts
|

Cross-cultural adaptation and validation of the Chinese version of the shoulder pain and disability index in patients with symptomatic shoulder pain

Abstract: The aim of this study is to cross-culturally adapt and translate the original version of SPADI into Chinese (C-SPADI), and to test the reliability, validity, and responsiveness of the C-SPADI.This research was a test of previously developed diagnostic criteria in a series of consecutive patients with universally applied gold standard. The original version was translated into Chinese according to international recognized standards. Patients who were diagnosed with a shoulder disorder and underwent shoulder arth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…The SPADI is translated into multiple languages. Cross‐cultural validation has been performed for the following languages: Spanish (11), Chinese (12), Arabic (13), Danish (14), Norwegian (15), Dutch (16), Indian (Tamil) (17), Hindi (18), Greek (19), Turkish (20), Brazilian Portuguese (21), Persian (22), Thai (23), Nepali (24), Italian (25), and German (26).…”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 99%
“…The SPADI is translated into multiple languages. Cross‐cultural validation has been performed for the following languages: Spanish (11), Chinese (12), Arabic (13), Danish (14), Norwegian (15), Dutch (16), Indian (Tamil) (17), Hindi (18), Greek (19), Turkish (20), Brazilian Portuguese (21), Persian (22), Thai (23), Nepali (24), Italian (25), and German (26).…”
Section: Shoulder Pain and Disability Index (Spadi)mentioning
confidence: 99%
“…Bone marrow edema of the humerus head is common in athletes engaged in throwing activities, but not common in the general population [25]. In this study, nearly 1/3 of PSSP patients showed bone marrow edema of the humerus, which was considered to be related to ischemia [26] or mechanical injury [17] caused by reduced blood supply to the shoulder joint after stroke. Bone marrow edema leads to increased intraosseous pressure and stimulates bone pain receptors in bone marrow, causing pain [27].…”
Section: Reviewmentioning
confidence: 61%
“…Translation, cross-cultural adaptation, and validation are necessary for direct international comparisons and cultural equivalence. Currently, the Western Ontario Rotator Cuff Index, 34 the Western Ontario Osteoarthritis of the Shoulder Index, 13 the Rotator Cuff Quality of Life Index, 35 and the Shoulder Pain and Disability Index 33 are available for application in Chinese patients, as well as the simplified Chinese version of the OSS developed in 2015. 39 Unevenly distributed wealth and educational resources as well as high illiteracy rates are prevailing challenges in most developing countries, and simplified patient-reported outcome measures are needed to overcome some of the resulting cultural and language barriers.…”
Section: Discussionmentioning
confidence: 99%
“…The average FS-OSS score was 24.23 ± 9.11 initially and 24.04 ± 8.75 in the retest taken 5 to 7 days later, with the median (interquartile range) being 24 (18-32) and 24 (17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32). The average initial SC-OSS was 25.56 ± 9.98, and it was 24.78 ± 9.51 during retesting, with the median (interquartile range) values of 25 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)(32)(33) and 24 (16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30)(31)…”
Section: Reliabilitymentioning
confidence: 98%